Relationship between cigarette smoking and the carbon monoxide concentration in the exhaled breath with perioperative respiratory complications - Ozgunay,Seyda Efsun (2018)
Abstract Background The purpose of the current study was to determine the effects of preoperative cigarette smoking and the carbon monoxide level in the exhaled breath on perioperative respiratory complications in patients undergoing elective laparoscopic cholecystectomies. Methods One hundred and fifty two patients (smokers, Group S and non-smokers, Group NS), who underwent laparoscopic cholecystectomies under general anesthesia, were studied. Patients completed the Fagerstrom Test for Nicotine Dependence. The preoperative carbon monoxide level in the exhaled breath levels were determined using the piCO+ Smokerlyzer 12 h before surgery. Respiratory complications were recorded during induction of anesthesia, intraoperatively, during extubation, and in the recovery room. Results Statistically significant increases were noted in group S with respect to the incidence of hypoxia during induction of anesthesia, intraoperative bronchospasm, bronchodilator treatment intraoperatively, and bronchospasm during extubation. The carbon monoxide level in the exhaled breath and the Fagerstrom Test for Nicotine Dependence, and number of cigarettes smoked 12 h preoperatively were designated as covariates in the regression model. Logistic regression analysis of anesthetic induction showed that a 1 unit increase in the carbon monoxide level in the exhaled breath level was associated with a 1.16 fold increase in the risk of hypoxia (OR = 1.16; 95% CI 1.01–1.34; p = 0.038). Logistic regression analysis of the intraoperative course showed that a 1 unit increase in the number of cigarettes smoked 12 h preoperatively was associated with a 1.16 fold increase in the risk of bronchospasm (OR = 1.16; 95% CI 1.04–1.30; p = 0.007). While in the recovery room, a 1 unit increase in the Fagerstrom Test for Nicotine Dependence score resulted in a 1.73 fold increase in the risk of bronchospasm (OR = 1.73; 95% CI 1.04–2.88; p = 0.036). Conclusions Cigarette smoking was shown to increase the incidence of intraoperative respiratory complications while under general anesthesia. Moreover, the estimated preoperative carbon monoxide level in the exhaled breath level may serve as an indicator of the potential risk of perioperative respiratory complications.